Modern opportunities of heart rate regulation in coronary heart disease - N. Sh. Zagidullin; D. F. Gareeva; B. I. Zagidullin; E. O. Travnikova; R. Kh. Zulkarneev; Sh. Z. Zagidullin (Российский кардиологический журнал)
It has been demonstrated that high heart rate (HR) levels are an independent risk factor of cardiovascular events and mortality from coronary heart disease and chronic heart failure (CHF). Recently, the so-called If-inhibitors which selectively block the pacemaker current in sinoatrial node cells (ivabradine, or Coraxan®) have been introduced to clinical practice. The latest large randomised clinical trials, such as SHIFT and BEAUTIFUL, have shown that in patients with stable effort angina, CHF, and HR >70 bpm, ivabradine reduces the incidence of cardiovascular end-points: myocardial infarction, coronary interventions, hospitalisations, and other events. These results justified the inclusion of ivabradine in the international clinical guidelines.